PENGARUH MOTIVASI BELAJAR, SARANA BELAJAR, DAN PERCAYA DIRI TERHADAP HASIL BELAJAR IPS SISWA PENERIMA BSM (BANTUAN SISWA MISKIN) SMP NEGERI DI SURABAYA - Murtiningsih, Murtiningsih (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This research aims to know (1) the influence of learning motivation towards learning outcomes students (2) influence of a learning tool toward student learning outcome (3) influence of confidence against a student learning outcome (4) influence of learning motivation, learning tools, and confident against the learning outcomes of students. This research uses a quantitative approach. Analysis of the multiple linear regression analysis was used. Population studies as many as 150 students taken in random sampling as much as 110 students in Junior High School State 39, 41, and 43 Surabaya school year 2014-2015. The results showed (1) there is the influence of learning motivation towards learning outcomes students (2) there is the influence of the means of learning towards student learning outcome (3) there are confident against influence student learning outcomes (4) there is the influence of learning motivation, learning tools, and confident against the results of student learning receiver BSM (poor students coupon) junior high school state Surabaya. Based on research it can be concluded that the motivation of learning, learning tools, and simultaneous confidence effect significantly to student learning outcomes, namely 94.4 whereas 5.6 is affected by other variables outside of the variables examined. To cover the shortfall, it can be done by way of teaching with the methods vary according to the material being taught by associate Social Science material in everyday life, learning tools are fitted and foster the confidence of students, so that the results of his studies.